Особливості формування соціально-комунікативних умінь дітей передшкільного віку у різних видах дитячої праці - Мартинова, Інна Едуардівна (My University, 2023)
Наукова робота присвячена аналізу такого аспекту проблеми соціалізації дітей передшкільного віку, як формування в них соціально- комунікативних умінь засобами видів дитячої праці. Розкрито сутнісні ознаки соціально-комунікативних умінь як психолого-педагогічної категорії та виявлено особливості їх формування стосовно дітей передшкільного віку. Надано класифікацію дитячої праці та характеристику кожного з її видів щодо формування соціально-комунікативних умінь у дітей. Проведено експериментальне дослідження з виявлення педагогічних умов формування соціально-комунікативних умінь дітей передшкільного віку. Розроблено і перевірено критерії та показники сформованості соціально-комунікативних умінь дітей 6-7 років. Виявлено та обґрунтовано три рівні сформованості означених умінь у дітей передшкільного віку. Запропоновано методику організації роботи з перевірки визначених педагогічних умов.
Martynova I.E. Peculiarities of the formation of social and communicative skills of preschool children in different types of child labor / Martynova I.E. - Qualification work. - Nizhin, 2023. – 91 p. The scientific work is devoted to the analysis of such an aspect of the problem of socialization of preschool children as the formation of their social and communicative skills by means of types of child labor. The essential features of social-communicative skills as a psychological-pedagogical category were revealed and the peculiarities of their formation in relation to preschool children were revealed. The classification of child labor and the characteristics of each of its types regarding the formation of social and communicative skills in children are provided. An experimental study was conducted to identify pedagogical conditions for the formation of social and communicative skills of preschool children. The criteria and indicators of the formation of social and communicative skills of children aged 6-7 years were developed and verified. Three levels of formation of the specified skills in preschool children were identified and substantiated. A method of organizing the work on checking the specified pedagogical conditions is proposed. Key words: socialization, communicative development, social-communicative development, сommunicative skills, social-communicative skills, types of child labor, children of preschool age.
Keywords: соціалізація; соціально- комунікативний розвиток; соціально-комунікативні уміння; трудове виховання дошкільників; передшкільний вік